Impact of SAA versus CRP in evaluation of acute-phase response in familial Mediterranean fever - Oguzhan Selvi; Bugra Han Egeli; Kerem Parlar; Elif Kilic Konte; Mustafa Akker; Mert Oztas; Sezgin Sahin; Amra Adrovic; Kenan Barut; Ibrahim Murat Bolayirli; Osman Simsek; Ozgur Kasapcopur; et al. (Medicine, 2026)
To compare the sensitivity and prognostic value of SAA and C-reactive protein (CRP) during familial Mediterranean fever (FMF) attacks and attack-free periods. Patients with juvenile idiopathic arthritis (JIA), acute appendicitis, and sepsis were used as controls. In this prospective study, 42 patients with FMF, 30 with JIA, and 30 with acute appendicitis were included. Blood samples for CRP and SAA were collected at 2 different time points: first, during an attack or preoperatively for acute appendicitis cases, and second, after the subsidence of the attack or postoperatively. To evaluate the role of SAA and CRP in the follow-up of inflammation, 42 patients with sepsis were studied serially. Twenty healthy individuals were also tested as controls. In appendectomy, JIA, and FMF patients, the mean CRP and SAA levels returned to normal values after operation/attack treatment. In both the inflammatory and non-inflammatory phases, a positive correlation was detected between CRP and SAA levels ( P < .001). In the sepsis group, mean SAA and CRP levels were 221.21 ± 95,05 and 402.2 ± 255.4 respectively. CRP and SAA levels were consecutively measured in 19 patients with sepsis, and a positive correlation was detected between these markers ( P < 0.01). In healthy controls, the SAA and CRP levels were within the normal ranges. We report that SAA and CRP levels were correlated in various disease settings. We suggest that CRP measurements are adequate for evaluating acute inflammatory conditions, and follow-up with SAA does not contribute to the early recognition of subclinical inflammation.